Effects of Active Versus Static Standing on Short-Duration Computer Task Performance, Postural Risks, Perceived Pain, Comfort and Fatigue. (September 2017) - Kar, Gourab; Guria, Sanjay; Peditto, Kathryn S.; Callan, Jacqueline R.; Fronsman, Andrea E.; Seo, Serena; Lee, Hyon; Stohler, Justine; Moon, Dan; Li, Manwen; Cackett, Megan A.; Hedge, Alan
This study evaluated the effects of active versus static standing on short-duration computer task performance, postural risks and perceived pain, comfort and fatigue. A repeated measures, within-subjects study was conducted in which 16 participants performed 40 trials of a computer-based homing task in two active standing versus a static standing condition. Computer task performance was operationalized using mousing and typing speed as the measures; postural risk was evaluated using the Rapid Entire Body Assessment (REBA). Perceived scores for pain, comfort and fatigue were reported through a survey administered at baseline and after each standing task condition. Results suggest that for short-duration computer tasks, there was no significant difference in typing speed between active and static standing. However, mousing speed was significantly higher in static standing compared to a specific active standing condition. Overall levels of perceived pain, comfort and fatigue did not differ significantly between active and static standing.